Functional characterization of putative ecdysone transporters in lepidopteran pests. (December 2022) - Samantsidis, George-Rafael; Fotiadou, Melina; Tzavellas, Savvas; Geibel, Sven; Nauen, Ralf; Swevers, Luc; Denecke, Shane; Vontas, John
Abstract: The insect steroid hormone ecdysone plays a critical role in insect development. Several recent studies have shown that ecdysone enters cells through O rganic A nion T ransporting P olypeptides (OATPs) in insects such as flies and mosquitoes. However, the conservation of this mechanism across other arthropods and the role of this transporter in canonical ecdysone pathways are less well studied. Herein we functionally characterized the putative ec dysone i mporter ( EcI) from two major agricultural moth pests: Helicoverpa armigera (cotton bollworm) and Spodoptera frugiperda (fall armyworm) . Phylogenetic analysis of OATP transporters across the superphylum Ecdysozoa revealed that EcI likely appeared only at the root of the arthropod lineage. Partial disruption of EcI in S. frugiperda decreased embryo hatching rate and larval survival, suggesting that this gene is essential for development in vivo . Depletion and re-expression of EcI in the lepidoptera cell line RP-HzGUT-AW1(MG) demonstrated this protein's ability to control ecdysone mediated signaling in gene regulation, its role in ecdysone mediated cell death, and its sensitivity to rifampicin, a well-known organic anion transporter inhibitor. Overall, this work sheds light on ecdysone uptake mechanisms across insect species and broadens our knowledge of the physiological roles of OATPs in the transportation of endogenous substrates. Graphical abstract: Image 1 Highlights: Disruption of EcI caused lethality in Spodoptera frugiperda . Removal of EcI decreased ecdysone import from cells. Re-expression of various orthologues of EcI in knockout cells rescued ecdysone import. Rifampicin inhibited EcI in vitro, highlighting the druggability of this protein.